Recreational development in the settlements of the Warta Valley in Wielkopolska - Januchta-Szostak, Anna; Karaśkiewicz, Agata (Turyzm/Tourism, 2018)
Riverside areas have substantial recreational and tourist assets, but their potential in the settlements of Wielkopolska is underused due to difficult access to the river and the poor development of the embankments. The aim of the research is to analyse the functional-spatial structure and the development of River Warta areas in the settlements of Wielkopolska with respect to their usefulness in recreation. Particular attention is paid to accessibility and the location of recreational infrastructure in the Warta Valley. Out of the eleven Wielkopolska settlements which were included, only in four – Konin, Śrem, Poznań and Sieraków – had sections of embankment boulevards been built. In the riverside areas there are few recreational facilities used in connection with the close proximity of the river. However, a great tourist asset of the Warta Valley is the Great Waterway Loop of Wielkopolska, which operates successfully due to the growing number of harbours and marinas in all the settlements included in the study.